The Use of Quizizz As An Online Assessment Application for Science Learning in The Pandemic Era - Darmawan, Melissa Salma; Daeni, Fitri; Listiaji, Prasetyo (Unnes Science Education Journal, 2020)
In the current pandemic era, learning process must be counduct online, including for assessment. To support online assessments, it is necessary to use information technology. A good and valid application for online assessment offered in this study is Quizizz. The purpose of this study is todetermine student responseapplication of online exams using the quizizz.The research subjects were students of science education, Universitas Negeri Semarang. The exam is a midterm of astronomy course. The method of research carried out includesthe applied method, responding to quizizz in conductinglearning assessments of multimedia learning. Theresults showed that students were very responsive tothe application of the quiz during the midterms, thoughthe mean score was still low (43.08% with a standard deviation of 15.83%), but students accepted the resultsand try to fix it. For the questionnaire, student responses to the use of Quizizz tend to be positive with the results of 8 statements getting positive responses of more than 50% of the total students.The Quizizz presents the problem with easeby analyzing the results of the detailed answers to help teachersor lecturers in carrying out the assessment.